Impact of Motivation on Compensation and Discipline at Musi Rawas Public Works - Suwarno Suwarno; Irma Idayati; Hardi Mulyono; Dewi Paramita; Efa Ayu Nabila (International Journal of Cyber ​​and IT Service Management (IJCITSM), 2025)
This study examines the effects of work discipline and compensation on employee performance, with work motivation as a moderating factor. Addressing critical challenges in public sector HR management, this research aims to understand how these variables interact to influence performance. A quantitative approach was adopted, with data collected from 62 respondents using observation, questionnaires, interviews, and documentation. The analysis methods included simple linear regression, correlation coefficients, t-tests, determination tests, and Moderated Regression Analysis (MRA). The findings reveal significant positive relationships between compensation and employee performance (tcalculate = 3.636 ≥ ttable = 1.670) and between work discipline and employee performance (tcalculate = 4.722 ≥ ttable = 1.670, R = 0.521). Furthermore, work motivation strengthens these relationships, amplifying their overall impact on performance. These results highlight the importance of timely compensation, robust disciplinary practices, and effective motivational strategies. Practical recommendations are provided for HR improvements within the Musi Rawas Public Works Department, and future research is encouraged to explore additional factors such as leadership and organizational culture.